The role of the tribal authority in managing human remains in South Africa: A local economic development perspective - Maphela, Bulelwa (International Journal of Innovative Research and Scientific Studies, 2025)
Managing human remains in South Africa is becoming increasingly challenging, and the communities most affected are those in rural areas. To investigate the role that tribal authority plays in managing human remains in KwaBhaca from a local economic development perspective, a focus group interview was conducted. An open-ended question approach was adopted to interview tribal council members, municipal representatives, community members, and emerging funeral directors. Four themes, social, political, environmental, and infrastructural, served as the basis for the interview. A thematic analysis was conducted based on the responses from the study participants. Findings revealed that the role of tribal authority in South Africa has evolved from handling communal matters to being part of the developmental agenda in rural areas. The study also revealed that rural areas still face infrastructural challenges such as road and water shortages, which hinder burial processes. The study concluded that the role of tribal authority is clearly articulated by the Department of Cooperative Governance and Traditional Affairs, and they have a mutually inclusive role in human remains management.